HangAmDan-B, an Ethnomedicinal Herbal Mixture, Suppresses Inflammatory Responses by Inhibiting Syk/NF-κB and JNK/ATF-2 Pathways - Yu, Tao (Mary Ann Liebert, Inc., 2013)
HangAmDan-B (HAD-B) is a powdered mixture of eight ethnopharmacologically characterized folk medicines that is prescribed for solid masses and cancers in Korea. In view of the finding that macrophage-mediated inflammation is a pathophysiologically important phenomenon, we investigated whether HAD-B modulates inflammatory responses and explored the associated molecular mechanisms. The immunomodulatory activity of HAD-B in toll-like receptor-activated macrophages induced by lipopolysaccharide (LPS) was assessed by measuring nitric oxide (NO) and prostaglandin E(2) (PGE(2)) levels. To identify the specific transcription factors (such as nuclear factor [NF]–κB and signaling enzymes) targeted by HAD-B, biochemical approaches, including kinase assays and immunoblot analysis, were additionally employed. HAD-B suppressed the production of PGE(2) and NO in LPS-activated macrophages in a dose-dependent manner. Furthermore, the extract ameliorated HCl/EtOH-induced gastritis symptoms. Moreover, HAD-B significantly inhibited LPS-induced mRNA expression of inducible NO synthase and cyclooxygenase (COX)-2. Interestingly, marked inhibition of NF-κB and activating transcription factor was observed in the presence of HAD-B. Data from direct kinase assays and immunoblot analysis showed that HAD-B suppresses activation of the upstream signaling cascade involving spleen tyrosine kinase, Src, p38, c-Jun N-terminal kinase, and transforming growth factor β–activated kinase 1. Finally, kaempferol, but not quercetin or resveratrol was identified as a bioactive compound in HAD-B. Therefore, our results suggest that HAD-B possesses anti-inflammatory activity that contributes to its anticancer property.